"Animal disease challenges" fifteen years later: The hypothesis in light of new data. (29th April 2017) - Gifford-Gonzalez, Diane
Abstract: Zooarchaeological evidence reflects cattle's central role among pastoral livestock for millennia in the once-green Sahara. However, zooarchaeological evidence attest to two chronologically separated, but similar delays in the entry of cattle into eastern and southern sub- Saharan Africa, where domestic caprines precede cattle as the earliest domestic livestock for several hundred years. In an earlier paper, I proposed that this delay in the introduction of cattle was due to the disease challenges presented to domestic bovines by the novel and grave epizoötiological threats by indigenous wild animals of sub-Saharan savannas, the preferred habitats of cattle. Herds of African buffalo and wildebeest, the latter absent from the Sahara-Sahel, are reservoirs of East Coast Fever (ECF) and wildebeest-derived malignant catarrhal fever (WD-MCF), respectively. Both pose serious veterinary challenges to bovine husbandry today and could have stalled the spread of pastoralism until their etiologies were understood and control measures developed by herders. The disease-challenge hypothesis could be falsified by discovering considerable cattle remains south of Lake Turkana between 4000 and 3000 BP. This paper reviews the hypothesis in light of the last 15 years' zooarchaeological research on early pastoralism in eastern Africa.